Exploring the Level of AI (Artificial Intelligence) Digital Literacy and Creative Thinking Skills in High School Students - Zebua, Nofamataro; Ibrohim, Ibrohim; Sulisetijono, Sulisetijono (Bioscientist : Jurnal Ilmiah Biologi, 2025)
The development of Artificial Intelligence (AI) in education has opened up opportunities for strengthening AI digital literacy and creative thinking skills among students. AI digital literacy includes understanding how AI works, the ethics of use, and utilization in various contexts, while creative thinking refers to the ability to generate innovative and original ideas. This study aims to explore the level of AI digital literacy and creative thinking skills among Xth grade high school students, using a descriptive method with proficiency tests and self-assessment questionnaires. The results showed that students' AI digital literacy level was low, with an average score of 56.94%, where students had difficulty in critically digesting information, recognizing the social impact of AI, using AI technology, and considering the ethical aspects of its use. In addition, students' creative thinking skills were also low, with an average score of 55.14%, especially in the aspects of originality of ideas, flexibility of thinking, and conceptual mapping. These findings highlight the need for the integration of an AI curriculum in education, the use of interactive AI tools, and the implementation of project-based learning models to improve students' AI digital literacy and creativity. In addition, learning environments that support exploration and positive feedback from teachers play an important role in creating optimal synergy between these two skills. Further research is needed to explore the limitations of AI in supporting creativity as well as the risks of technology dependency in the innovative thinking process.